2013
DOI: 10.1093/nar/gkt675
|View full text |Cite
|
Sign up to set email alerts
|

Non-FG mediated transport of the large pre-ribosomal subunit through the nuclear pore complex by the mRNA export factor Gle2

Abstract: Multiple export receptors passage bound pre-ribosomes through nuclear pore complexes (NPCs) by transiently interacting with the Phe-Gly (FG) meshwork of their transport channels. Here, we reveal how the non-FG interacting yeast mRNA export factor Gly-Leu-FG lethal 2 (Gle2) functions in the export of the large pre-ribosomal subunit (pre-60S). Structure-guided studies uncovered conserved platforms used by Gle2 to export pre-60S: an uncharacterized basic patch required to bind pre-60S, and a second surface that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…However, because Bud20 does not recruit Crm1 in vitro (Altvater et al 2012), this NES-like element may not be functionally active. Besides these export factors, the protein Gle2 ensures efficient nuclear export of the pre-60S particle by engaging in non-FG interactions with the nucleoporin Nup116 (Occhipinti et al 2013). Additionally, the HEAT-repeat containing proteins Sda1 (Dez et al 2006) and Rrp12 (Oeffinger et al 2004) have been reported to contribute to pre-60S nuclear export.…”
Section: Maturation Of the Central Protuberance And Checkpoint Contromentioning
confidence: 99%
“…However, because Bud20 does not recruit Crm1 in vitro (Altvater et al 2012), this NES-like element may not be functionally active. Besides these export factors, the protein Gle2 ensures efficient nuclear export of the pre-60S particle by engaging in non-FG interactions with the nucleoporin Nup116 (Occhipinti et al 2013). Additionally, the HEAT-repeat containing proteins Sda1 (Dez et al 2006) and Rrp12 (Oeffinger et al 2004) have been reported to contribute to pre-60S nuclear export.…”
Section: Maturation Of the Central Protuberance And Checkpoint Contromentioning
confidence: 99%
“…Gle2 is also involved in the mRNA export pathway, especially under stress conditions (Occhipinti et al, 2013). Similar to mutations in MEX67 and MTR2, alleles of GLE2 have been identified that specifically impair pre-60S export but leave mRNA export intact, indicating that the two export roles of Gle2 are separable (Oeffinger et al, 2009;Yao et al, 2008).…”
Section: Nuclear Export Of Pre-60s Subunitsmentioning
confidence: 99%
“…Curiously, the recruitment of Gle2 to pre-60S subunits requires its prior tethering to the Gle2-binding sequence (GLEBS) of the nucleoporin Nup116. However, like ARX1, ECM1, and BUD20, GLE2 genetically interacts with pre-60S export factors and double mutants display pre-60S export defects (Occhipinti et al, 2013).…”
Section: Nuclear Export Of Pre-60s Subunitsmentioning
confidence: 99%
“…particle via a basic patch on its the surface, which is distinct from the interaction surface for pre-mRNPs, and forms an interaction with Nup116 that is necessary for NPC translocation [185].…”
Section: Accepted Manuscriptmentioning
confidence: 99%